2008
DOI: 10.1007/s12355-008-0039-4
|View full text |Cite
|
Sign up to set email alerts
|

Sugar beet performance under newly reclaimed soils conditions of Sinai, Egypt

Abstract: The present investigation was carried out to study the effect of planting and harvesting time on yield and quality of sugar beet cultivars under North Sinai conditions.Two field experiments were conducted in a newly reclaimed sandy soil in a private farm at North Sinai region to study the effect of three sowing dates (1 st Aug., 1 st Sep. and 1 st Oct.) and three harvesting dates (170, 190 and 210 days after planting) on yield and quality of six sugar beet cultivars, viz.,Pamela, Hipoly2, Pleno, Monte Bianco,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
(13 reference statements)
2
4
0
Order By: Relevance
“…Sowing sugar beet on October 1 st significantly increased by 1.03%, 1.11% and 1.17% in sucrose%, CS% and QI%, successively compared to that sown on November 1 st . These results are in agreement with those obtained by Mahdi et al (2013) and Nasr and Abd El-Razek (2008).…”
Section: Results and Discutionssupporting
confidence: 94%
See 1 more Smart Citation
“…Sowing sugar beet on October 1 st significantly increased by 1.03%, 1.11% and 1.17% in sucrose%, CS% and QI%, successively compared to that sown on November 1 st . These results are in agreement with those obtained by Mahdi et al (2013) and Nasr and Abd El-Razek (2008).…”
Section: Results and Discutionssupporting
confidence: 94%
“…Sowing date has an active role on growth, yield and quality characteristics of sugar beet under the environmental conditions of Egypt; there is a general agreement that early planting of sugar beet during September-October results in highest sucrose % as well as root and sugar yields per unit area (Nasr and Abd El-Razek 2008). Important environmental variables that determine the beginning of sugar beet growing season are temperature, light precipitation and soil moisture (Petkeviciene, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The superiority of Demo (V 2 ) variety might due to its increased photosynthetic efficiency. These effects are in agreement with those obtained by Masri (2008), Nasr & Abd El-Razek (2008), Safina et al (2012), Neamatollahi et al (2013), Masri & Hamza (2015) and Mekdad & Rady (2016) who reported that root weight and yield as well as sucrose % and sugar yield were differed significantly by varies varieties.…”
Section: Effect Of Two Sugar Beet Varietiessupporting
confidence: 92%
“…The beet sugar industry in the tropical and subtropical regions, which are mostly developing countries (includ-reason is that sugar beet could be a possible solution as a tolerant crop of soil alkalinity or for newly reclaimed soils, which are common in tropical and subtropical areas (Abo-Elwafa et al, 2006;Mawusi, 2004;Nasr & Abd El-Razek, 2008). Cultivation of sugar beet in developing countries could be profitable for farmers in two ways: (a) by diversifying their incomes by enabling them to grow an additional cash crop, and (b) by supplying sugar factories with raw material in addition to the sugar cane that will extend the factories' supply for up to 10 mo of the year (Balakrishnan & Selvakumar, 2009;Mandere, Persson, Anderberg, & Pilesjo, 2010).…”
Section: Introductionmentioning
confidence: 99%